Carcinosarcoma of the bladder: case report and review of the literature - Akoluk, Arda; Barazani, Yagil; Slova, Denisa; Shah, Sovrin; Tareen, Basir (Canadian Urological Association Journal, 2013)
Primary osteosarcomas of the bladder account for about 0.04% of bladder neoplasms. Most of the patients in the literature expired within 6 months and, in almost all of the cases in the literature, radical cystectomy with postoperative chemotherapy was the treatment choice. A 79-year-old gentleman presented with gross hematuria. Cystoscopy demonstrated a 2- to 3-cm tumour along the lateral wall of the bladder. The tumour was resected incompletely via initial transurethral resection of bladder tumour (TURBT), and a second TURBT was subsequently performed to fully resect the residual mass. Surgical pathology from these 2 resections revealed osteosarcoma with invasion into the muscularis propria. A cystoprostatectomy was performed and final pathologic specimen revealed high-grade CIS without evidence of residual osteosarcoma. Postoperatively, the patient did not receive chemotherapy or radiation and currently remains disease-free 2 years post-radical cystectomy. Only 33 well-documented cases of primary osteosarcoma of the bladder have been reported to date. However, there are only 3 cases in which TURBT resulted in complete resection.